Therapeutic Efficacy of an Fc-Enhanced TCR-Like Antibody to the Intracellular WT1 Oncoprotein - Veomett, Nicholas (2014)
PURPOSE: RMFPNAPYL (RMF), a WT1-derived CD8 T cell epitope presented by HLA-A*02:01, is a validated target for T-cell-based immunotherapy. We previously reported ESK1, a high avidity (Kd < 0.2nM), fully-human monoclonal antibody (mAb) specific for the WT1 RMF peptide/HLA-A*02:01 complex, which selectively bound and killed WT1+ and HLA-A*02:01+ leukemia and solid tumor cell lines. EXPERIMENTAL DESIGN: We engineered a second-generation mAb, ESKM, to have enhanced antibody dependent cell-mediated cytotoxicity (ADCC) function due to altered Fc glycosylation. ESKM was compared to native ESK1 in binding assays, in vitro ADCC assays, and mesothelioma and leukemia therapeutic models and pharmacokinetic studies in mice. ESKM toxicity was assessed in HLA-A*02:01+ transgenic mice. RESULTS: ESK antibodies mediated ADCC against hematopoietic and solid tumor cells at concentrations below 1µg/ml, but ESKM was about 5–10 fold more potent in vitro against multiple cancer cell lines. ESKM was more potent in vivo against JMN mesothelioma, and effective against SET2 AML and fresh ALL xenografts. ESKM had a shortened half-life (4.9 vs 6.5 days), but an identical biodistribution pattern in C57BL6/J mice. At therapeutic doses of ESKM, there was no difference in half-life or biodistribution in HLA-A*02:01+ transgenic mice compared to the parent strain. Importantly, therapeutic doses of ESKM in these mice caused no depletion of total WBCs or hematopoetic stem cells, or pathologic tissue damage. CONCLUSIONS: The data provide proof of concept that an Fc-enhanced mAb can improve efficacy against a low-density, tumor-specific, peptide/MHC target, and support further development of this mAb against an important intracellular oncogenic protein.